Evidence for a peptidoglycan‐like structure in Orientia tsutsugamushi. Issue 3 (19th June 2017) - Atwal, Sharanjeet; Giengkam, Suparat; Chaemchuen, Suwittra; Dorling, Jack; Kosaisawe, Nont; VanNieuwenhze, Michael; Sampattavanich, Somponnat; Schumann, Peter; Salje, Jeanne
Summary: Bacterial cell walls are composed of the large cross‐linked macromolecule peptidoglycan, which maintains cell shape and is responsible for resisting osmotic stresses. This is a highly conserved structure and the target of numerous antibiotics. Obligate intracellular bacteria are an unusual group of organisms that have evolved to replicate exclusively within the cytoplasm or vacuole of a eukaryotic cell. They tend to have reduced amounts of peptidoglycan, likely due to the fact that their growth and division takes place within an osmotically protected environment, and also due to a drive to reduce activation of the host immune response. Of the two major groups of obligate intracellular bacteria, the cell wall has been much more extensively studied in the Chlamydiales than the Rickettsiales . Here, we present the first detailed analysis of the cell envelope of an important but neglected member of the Rickettsiales, Orientia tsutsugamushi . This bacterium was previously reported to completely lack peptidoglycan, but here we present evidence supporting the existence of a peptidoglycan‐like structure in Orientia, as well as an outer membrane containing a network of cross‐linked proteins, which together confer cell envelope stability. We find striking similarities to the unrelated Chlamydiales, suggesting convergent adaptation to an obligate intracellular lifestyle. Abstract : Orientia tsutsugamushi is an obligate intracellular bacterium of the family Rickettsiaceae. It is insensitive to ß‐lactam antibiotics and was previously thought to completely lack peptidoglycan, which is unusual amongst bacteria but can be tolerated in the osmotically protected intracellular replicative niche. Here we use a combination of mass spectrometry, gene expression analysis, drug sensitivity assays and D‐alanine probes to present the first direct evidence for a minimal peptidoglycan‐like structure in this organism.